Occupational Ergonomics in Industrially Developing Countries - Gangopadhyay, Somnath (International Journal of Occupational Safety and Health, 2012)
DOI: http://dx.doi.org/10.3126/ijosh.v2i2.6564 International Journal of Occupational Safety and Health, Vol 2. No 2 (2012) 1-2